THE ROLE OF PANCASILA IN FIGHTING RADICALISM AND SEPARATISM - Nugraha, Naufal Aditya; Habibah, Siti Maizul (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2023)
The phenomenon of the development of radicalism and separatism in society or understanding or ideology shows the potential for the disintegration of Pancasila. Pancasila as the source of values and the basis of the state cannot fully carry out its role in overcoming the problem of radicalism and separatism that is widespread among the people. Internal and external factors play an important role in the emergence of radicalism and separatism which leads to terrorism and the division of society. It is important to find the right way to qualify the criteria and values of Pancasila. The research method uses critical research methods and social phenomenology. The sources of information used in this study come from news, scientific journals and research from several related experts.The results showed that the efforts of the Pancasila method to overcome the problem of radicalism and separatism in Indonesia are very important and necessary for the state and society. Pancasila must be a value system and state system that must be strengthened through the establishment of standard criteria and value propositions that can be recognized at all levels of society.